2018
DOI: 10.1080/12298093.2018.1454013
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Evaluation of Yeast Antagonists for Biological Control ofBotrytis cinereaon Strawberry Fruits

Abstract: Gray mold (Botrytis cinerea) is one of the most common diseases of strawberries (Fragaria × ananassa Duchesne) worldwide. Although many chemical fungicides are used for controlling the growth of B. cinerea, the risk of the fungus developing chemical resistance together with consumer demand for reducing the use of chemical fungicides have necessitated an alternative method to control this pathogen. Various naturally occurring microbes aggressively attack plant pathogens and benefit plants by suppressing disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 52 publications
3
71
0
Order By: Relevance
“…However, A. subglaciale (AS14) that showed the highest efficacy in reducing B. cinerea colony growth in in vitro assay, performed worse than A. pullulans in vivo. This phenomenon is not uncommon and was also observed in various previous studies (Chen et al 2018 ). Conversely, Di Francesco et al ( 2015 ) showed how A. pullulans strains L1 and L8 were more effective in the control of B. cinerea on apple than in inhibiting fungal conidial germination, displaying a reduction of the pathogen lesion diameter of 88.9% and 94.4% respectively.…”
Section: Discussionsupporting
confidence: 83%
“…However, A. subglaciale (AS14) that showed the highest efficacy in reducing B. cinerea colony growth in in vitro assay, performed worse than A. pullulans in vivo. This phenomenon is not uncommon and was also observed in various previous studies (Chen et al 2018 ). Conversely, Di Francesco et al ( 2015 ) showed how A. pullulans strains L1 and L8 were more effective in the control of B. cinerea on apple than in inhibiting fungal conidial germination, displaying a reduction of the pathogen lesion diameter of 88.9% and 94.4% respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Unanimously, studies performed so far recommend VOCs application under air-tight environment, in order to rapidly saturate the atmosphere with the volatile antimicrobials. Particularly effective application of VOCs is reported in the control of storage pathogens on fresh fruit (e.g., citrus, peach, strawberry) but also other commodities such as nuts, grains, and seeds (Table 1; Strobel, 2006;Fialho et al, 2011;Wang et al, 2013;Chen et al, 2018;Gao et al, 2018). Bacteria produce volatile metabolites as part of their normal metabolism ( Figure 1A).…”
Section: Volatile Organic Compounds Of Microbial Originmentioning
confidence: 99%
“…The mycelium discs of both fungi were placed 6 cm apart on culture medium in opposite sides of the plate. In the control, B. cinerea mycelium was inoculated in both sides of the plates [ 15 ]. After 10 days of incubation in the dark at 22 °C, the radial mycelial growth of B. cinerea towards the endophytic fungus (Ri) and radial mycelial growth of B. cinerea on a control plate (Rc) were measured and the percentage of inhibition was calculated according to the formula (Rc−Ri)/Rc × 100.…”
Section: Methodsmentioning
confidence: 99%